Development of Oriented Learning Devices of Model Eliciting Activities to Improve Math Abtraction Ability SMK Students - Desniarti Desniarti; Muhammad Hafiz (Indonesian Journal of Education, Social Sciences and Research (IJESSR), 2020)
This study aims to determine the effectiveness of learning tools oriented Model Eliciting Activities (MEAs) to improve students' mathematical abstraction and selfefficacy  abilities. Learning tools developed (LKPD, RPP, Mathematical Abstraction Ability Test ). The quality of products developed is assessed based on aspects of validity, practicality, and effectiveness. The procedure for developing learning tools refers to the 4-D development model, namely Define, Design, Develop, and Disseminate. Due to the limitations of researchers, the study was carried out to the develop stage. The subjects of this study were students of SMK Al Washliah 4 Medan. The instruments used to measure the quality of learning tools developed were learning assessment sheets to measure validity, student response questionnaires and observation sheets for the implementation of learning activities to measure practicality, problem solving ability tests to measure effectiveness.